CFD modeling of heat transfer in a rectangular channel with dimplepin finning - Spokoiny, M. Yu.; Trofimov, V. E.; Shevchuk, M. V. (Technology and design in electronic equipment, 2013)
Using the CFD modeling method, the authors have investigated conjugate heat transfer in a rectangular channel with dimple-pin finning with hight of pins, depth of cavities and Reynolds number values varying in the range, characteristic for heat exchangers designed for liquid cooling of microelectronic devices, such as microprocessors. Criterion dependencies for calculation of heat transfer under these conditions have been obtained.